Pythochemical analysis and acute oral toxicity study of the ethanolic leaves extract of Plectranthus amboinensis (Lour) Spreng - Ramli, Norazsida; Oothuman, Pakeer; Bakhtiar, M. Taher; El-Hady Sayed Ahmed, Hassan Mohammed (2012)
Phytochemical analysis on the crude ethanolic extract of leaves of Malaysian Plectranthus amboinensis (Lour) Spreng was carried out to delineate the presence of its chemical constituents like Alkaloid, Flavonoid, Saponin, Triterpenoid, Steroid, and Phenolic. Acute oral toxicity at one dose level of 5000 mg/kg as per OECD Guideline for Testing of Chemicals 423 was conducted to evaluate the safeness of this extract to be consumed by humans. 20 mice were divided into one control group and one experimental group. All the mice were observed for signs of toxicity, mortality, weight changes and gross pathological changes. Results on phytochemical analysis showed only flavanoid was present in the extract. The acute oral toxicity test revealed that no mortality or evidence of adverse effects were seen in the treated mice. Studies on histopathological examination of kidneys and liver showed normal architecture suggesting no morphological changes. Thus this ethanolic extract of leave P. amboinensis can be considered as safe as it did not cause either any lethality or adverse changes in mice.